Frequency domain filtering strategies for hybrid optical information processing - Chatwin, C. R. (Electronic & electrical engineering research studies. Pattern recognition & image processing series, 1996)
The book focuses attention on the development of optically implementable frequency domain algorithms that may be exploited to enhance the performance of optical information processing systems. The objective of filtering is to overcome limitations in performance that are generated by problems relating to input image distortion, noise, clutter, discrimination, object localisation, accuracy, multi-class recognition and optical efficiency. The methods and architectures reported will be of great interest to researchers and industrial companies building systems for industrial inspection, security and surveillance, military acquisition and tracking.